2004
DOI: 10.1002/ejic.200300709
|View full text |Cite
|
Sign up to set email alerts
|

The First Cyclometallated (1‐Ferrocenylethanone thiosemicarbazone)palladium(II) Compounds − Crystal and Molecular Structure of [Pd{(η5‐C5H5)Fe(η5‐C5H3)C(Me)=NN=C(S)NHMe}(PPh3)]

Abstract: Treatment of the 1‐ferrocenylethanone thiosemicarbazone ligands (η5‐C5H5)Fe(η5‐C5H4)C(Me)=NN(H)C(=S)NHR [R = H (a), Me (b)] with K2[PdCl4] gave the novel heterometallic octanuclear palladium(II) compounds [Pd{(η5‐C5H5)Fe(η5‐C5H3)C(Me)=NN=C(S)NHR}]4 [R = H (1a), Me (1b)] as tetramers, after deprotonation of the NH group, with the ligands acting as terdentate donors through the [C,N,S] atoms. Treatment with nucleophiles cleaves the tetrameric clusters giving compounds in which splitting only of the Pd−Sbridging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The upfield shift of the H5 and H11 resonances (as compared to 3a and 1b) was due to shielding by the phosphine phenyl rings [32,33], confirming coordination of the ligand. The 31 P-{ 1 H} NMR spectra showed a singlet resonance at ca.…”
Section: Crystal Structure Of 3amentioning
confidence: 87%
“…The upfield shift of the H5 and H11 resonances (as compared to 3a and 1b) was due to shielding by the phosphine phenyl rings [32,33], confirming coordination of the ligand. The 31 P-{ 1 H} NMR spectra showed a singlet resonance at ca.…”
Section: Crystal Structure Of 3amentioning
confidence: 87%
“…Transition metal complexes involving organic-TSCs have emerged as a new alternative to current therapeutic agents [32][33][34][35][36][37][38]. In this regard, we report the synthesis and biological evaluation of cyrhetrenyl and ferrocenyl thiosemicarbazones as potential trypanocidal and antitubercular agents [39].…”
mentioning
confidence: 98%
“…Because of the ring-current effect, a pronounced tendency towards line broadening was observed for 2 in the nonpolar solvent CDCl 3 . The 1 H NMR spectrum of 2 in [D 6 ]acetone showed that the ring current shields the NH protons and induces large upfield shifts, and as a consequence, the chemical shifts of the two NH protons appear at δ = 2.57 and 2.82 ppm, respectively. There are three peaks corresponding to the substituted Cp ring at δ = 3.76, 4.39, and 4.72 ppm.…”
Section: Resultsmentioning
confidence: 98%
“…The reaction of Ru 3 (CO) 12 with acetylferrocene thiosemicarbazone in thf at 40°C was also monitored by positiveion ESI-MS analysis. As shown in Figure 4, after heating the reaction system for 30 min, peaks are observed at m/z = 785 and 813, values typical for carbonyl loss from Ru 3 (CO) 9 [L-H] and corresponding to the ions Ru 3 (CO) 6 [L-H] and Ru 3 (CO) 7 [L-H], respectively. A peak corresponding to dinuclear compound Ru 2 (CO) 4 [L] 2 is also observed at m/z = 942.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation